2012
DOI: 10.1074/jbc.m112.418533
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular Endothelin Type B Receptor-driven Ca2+ Signal Elicits Nitric Oxide Production in Endothelial Cells

Abstract: Background:The intracrine nature of endothelin-1 is largely correlated with nuclear signaling events. Results: In endothelial cells, endothelin-1 acting on endolysosomal ET B receptors increases cytosolic Ca 2ϩ and nitric oxide. Conclusion: Endolysosomal ET B receptors are functional. Significance: We identify a new pathway for ET-1-induced intracrine signaling and provide the first evidence that intracellular G protein-coupled receptors are involved in redox signaling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 60 publications
0
16
0
Order By: Relevance
“…However, the Ca 2ϩ response pattern was strikingly different in the two paradigms. Extracellular administration of LPI resulted in a relatively slow response that reached a peak within 1-2 min and continued with a plateau phase, whereas LPI microinjection induced a fast and transitory effect similar to that reported upon activation of other intracellular GPCRs, such as those for angiotensin II (29,33,62) or endothelin 1 (28). We have noticed likewise discrepancies in the plasmalemmal-initiated versus intracellularly initiated Ca 2ϩ responses by the G protein-coupled estrogen receptor GPER/GPR30 (34,63), which is reportedly expressed at both sites (64,65).…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…However, the Ca 2ϩ response pattern was strikingly different in the two paradigms. Extracellular administration of LPI resulted in a relatively slow response that reached a peak within 1-2 min and continued with a plateau phase, whereas LPI microinjection induced a fast and transitory effect similar to that reported upon activation of other intracellular GPCRs, such as those for angiotensin II (29,33,62) or endothelin 1 (28). We have noticed likewise discrepancies in the plasmalemmal-initiated versus intracellularly initiated Ca 2ϩ responses by the G protein-coupled estrogen receptor GPER/GPR30 (34,63), which is reportedly expressed at both sites (64,65).…”
Section: Discussionmentioning
confidence: 90%
“…The accumulating evidence pointing to endolysosomes as intracellular locations where GPCRs initiate signaling (19,24,28,69) prompted us to probe for colocalization of GFP-tagged GPR55 and RFP-tagged Rab7, an endolysosomal-associated small GTPase (46). We noticed extensive colocalization of GPR55 and Rab7.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…41 We also showed that platelet NO production by individual platelets temporally follows the increase in cytosolic Ca 11 concentration, because in the majority of platelets (.90%), fluorescence for NO was preceded by an intracellular Ca 11 increase, similarly to what was previously shown in smooth muscle cells 42 and endothelial cells. [43][44][45][46] The lag time between the 2 events in platelets (33 6 9.5 s) seems to be longer than that reported in vascular endothelial cells stimulated with bradykinin, in which a delay of ;5 seconds was observed, 45 or in human umbilical cord endothelial cells stimulated with histamine, 46 or in porcine aortic endothelial cells stimulated with thrombin, where almost no lag phase between the 2 events was observed. 47 These apparent discrepancies could be explained considering the different roles played by endothelial-released and platelet-released NO.…”
Section: Blood 22 January 2015 X Volume 125 Number 4 Platelet Nitrimentioning
confidence: 55%